ANALISIS BENTUK PENYIASATAN STRUKTUR PADA NOVEL RUMAH TANPA JENDELA KARYA ASMA NADIA - Kapsah, Kapsah; Husnul Mawadah, Ade; Tisnasari, Sundawati (Bahtera Indonesia, 2020)
This study analyzes the novel using a statistical approach. The research method is a qualitative-descriptive method. The purpose of this study is to describe the form of structuring that is contained in the novel House without Windows by Asma Nadia. As for data collected through library research research techniques, see techniques and note techniques. The data used in this study are excerpts from the novel that are the source of the data. The source of the data in this study is the novel House without Windows by Asma Nadia. In addition, the data obtained are classified based on their shape in order to facilitate the analysis. Data analyzed are data that have been tested for validity by validators who are experts in their fields. Referring to the knife analysis of the stylistic approach, we found a form of structural alignment. So, it can be concluded that the form of structuring data obtained from the novel House without Window by Asma Nadia 55 data with detailed data, 9 data repetition, 4 data parallelism, 7 data anaphora, 9 data antithesis, 7 data alliteration, climax as much as 1 data, asindeton as much as 13 data, rhetorical questions as much as 4 data, and polisidenton as much as 1 data. While the least data found was polysindeton and climax data, and no anticlimactic data was found.